San Juan Boundary Arbitration atlas [map 7] ... - Kellett, Henry, 1806-1875 (University of Victoria Libraries, 2020)
San Juan Boundary Arbitration. Atlas (10 maps with list). [Juan de Fuca, Strait, 1849; 1871]. Admiralty Chart 1911. [Map 7]. America, N.W. Coast. Strait of Juan de Fuca. Surveyed by Captain Henry Kellett, R.N. 1847, Haro & Rosario straits, by Captain G. H. Richards, R.N. 1858, Admiralty inlet and Puget sound, by the United States Exploring Expedition, 1841, coast south of C. Flattery by the same in 1853 J. & C. Walker sculpt. Published Jany. 18th. 1849; Corrections to 1871; Soundings in fathoms. Insets: Continuation of Admiralty inlet and Puget sound; side view title: Appearance of Cape Flattery bearing N.E. 16 or 17 miles. Relief shown by hachures and spot heights; depths shown by soundings in fathoms. Shows First Nations villages. ...